OncoAlert Round Table Discussions: The Global COVID-19 Experience. (2021) - Morgan, Gilberto; de Azambuja, Evandro; Punie, Kevin; Ades, Felipe; Heinrich, Kathrin; Personeni, Nicola; Rahme, Ramy; Ferrara, Roberto; Pels, Kevin; Garassino, Marina; von Bergwelt-Baildon, Michael; Lopes, Gilberto; et al.
Abstract : The speed and spread of the COVID-19 pandemic has been affecting the entire world for the past several months. OncoAlert is a social media network made up of more than 140 oncology stakeholders: oncologists (medical, radiation, and surgical), oncology nurses, and patient advocates who share the mission of fighting cancer by means of education and dissemination of information. As a response to the COVID-19 pandemic, OncoAlert hosted The Round Table Discussions. We have documented this effort along with further discussion about the COVID-19 pandemic and the consequences on patients living with cancer to disseminate this information to our colleagues worldwide.